Shifts in indigenous culture relate to forest tree diversity: A case study from the Tsimane', Bolivian Amazon. (June 2015) - Guèze, Maximilien; Luz, Ana Catarina; Paneque-Gálvez, Jaime; Macía, Manuel J.; Orta-Martínez, Martí; Pino, Joan; Reyes-García, Victoria
Highlights: Tree alpha diversity is significantly associated with Tsimane' cultural change. Tree alpha diversity peaks in villages with intermediate levels of cultural change. Different indigenous practices represent a gradient of human disturbance. Tree diversity changes are subtle and best understood with ground data. Abstract: Understanding how indigenous peoples' management practices relate to biological diversity requires addressing contemporary changes in indigenous peoples' way of life. This study explores the association between cultural change among a Bolivian Amazonian indigenous group, the Tsimane', and tree diversity in forests surrounding their villages. We interviewed 86 informants in six villages about their level of attachment to traditional Tsimane' values, our proxy for cultural change. We estimated tree diversity (Fisher's Alpha index) by inventorying trees in 48 0.1-ha plots in old-growth forests distributed in the territory of the same villages. We used multivariate models to assess the relation between cultural change and alpha tree diversity. Cultural change was associated with alpha tree diversity and the relation showed an inverted U-shape, thus suggesting that tree alpha diversity peaked in villages undergoing intermediate cultural change. Although the results do not allow for testing the direction of the relation, we propose that cultural change relates to tree diversity through the changes in practices and behaviors that affect the traditional ecological knowledge of Tsimane' communities; further research is needed to determine the causality. Our results also find support in the intermediate disturbance hypothesis, and suggest that indigenous management can be seen as an intermediate form of anthropogenic disturbance affecting forest communities in a subtle, non-destructive way.